PEDAGOGICAL AND PSYCHOLOGICAL MECHANISMS OF USING ARTIFICIAL INTELLIGENCE IN DEVELOPING METACOGNITIVE COMPETENCES (Universal International Scientific Journal, 2026)
This article analyzes the psychological and pedagogical mechanisms of using artificial intelligence technologies to develop metacognitive competencies in students in the modern educational process. The study highlights the psychological essence of metacognitive competence, its structural components, and its role in managing a person's cognitive processes. It also studies the potential of artificial intelligence-based educational platforms to develop psychological processes such as self-regulated learning, reflective thinking, motivation, and critical thinking in students. The article develops psychological mechanisms for the formation of metacognitive competencies and practical recommendations for their effective use in the educational process.
Keywords: metacognitive competence; artificial intelligence; psychological mechanisms